PENGAMALAN BUDAYA SIPAMANDAQ DI PERUSDA ANEKA USAHA MAJENE DALAM REALISASI PERTANGGUNGJAWABAN SOSIAL DAN LINGKUNGAN - Rahim, Nur hidayah; Ilyas, Herlina (Lembaga Penelitian, Publikasi dan Pengabdian Pada Masyarakat, 2023)
Cultural aspects in accounting can determine the behavior of accountants, the accounting process, and the accounting reports made by the company. For regional companies, local wisdom is actually a core value that can be used as a reference in business management, including accounting processes. Sipamandaq is a culture of the Mandar tribe which is still rarely researched, especially in relation to social and environmental responsibility for companies operating around the Mandar tribe area, including the Perusda Aneka Usaha Majene. This research aims to determine the actualization of Sipamandaq culture in the efforts of Perusda Aneka Usaha Majene to realize social and environmental responsibility. The research method uses a qualitative method with an ethnographic approach where data is obtained through in-depth interviews and document studies, especially financial reports. The conclusion of the research is that Perusda Aneka Usaha Majene has not realized social and environmental responsibility optimally where its contribution does not fulfill the main value of sipamandaq, namely protecting each other, but has made efforts to realize other values, namely sirondo-rondoi (cooperation), siamasei (loving each other), and sianuang pa 'mai (difficult and difficult, happy and happy) by supporting the operations of the regional government of Majene Regency.